A STUDY ON THE RURAL DEVELOPMENT MODEL IN KOREAN SAEMAEUL MOVEMENT BASED ON THE THEORY OF LOCAL NETWORK GOVERNANCE - Tri, Tran Huu (VNU Journal of Foreign Studies; Vol 34 No 6, 2018)
The article focuses on the Korean Saemaeul movement based on the theory of Local Network Governance. Network Governance, which emphasizes the role, organic collaboration between actors in solving social problems or rural development, is a very important theory to evaluate and analyze the rural development movement. As a whole, the rural development process is shaped by three main actors: the central, the local and the local people and, depending on the level of cooperation and interactions of these actors, the degree of achievement are also different. Through this paper, we hope to suggest a model of rural development in Vietnam based on the theory of Local Network Governance and the Korean Saemaeul movement.